Characterisation and optimisation of targets for plasma wakefield acceleration at SPARC_LAB. (1st April 2022) - Costa, G; Anania, M P; Arjmand, S; Biagioni, A; Del Franco, M; Del Giorno, M; Galletti, M; Ferrario, M; Pellegrini, D; Pompili, R; Romeo, S; Rossi, A R; et al.
Abstract: One of the most important features of plasma-based accelerators is their compactness because plasma modules can have dimensions of the order of mm cm − 1, providing very high-accelerating fields up to hundreds of GV m − 1 . The main challenge regarding this type of acceleration lies in controlling and characterising the plasma itself, which then determines its synchronisation with the particle beam to be accelerated in an external injection stage in the laser wakefield acceleration (LWFA) scheme. This issue has a major influence on the quality of the accelerated bunches. In this work, a complete characterisation and optimisation of plasma targets available at the SPARC_LAB laboratories is presented. Two plasma-based devices are considered: supersonic nozzles for experiments adopting the self-injection scheme of laser wakefield acceleration and plasma capillary discharge for both particle and laser-driven experiments. In the second case, a wide range of plasma channels, gas injection geometries and discharge voltages were extensively investigated as well as studies of the plasma plumes exiting the channels, to control the plasma density ramps. Plasma density measurements were carried out for all the different designed plasma channels using interferometric methods in the case of gas jets, spectroscopic methods in the case of capillaries.